'Words of wisdom': text, voice and justice in I, Daniel Blake - Jones, Susan (Taylor & Francis, 2017)
The film, I, Daniel Blake, has received critical acclaim for its portrayal of the experiences of those attempting to navigate the bureaucracy of the British welfare state system. In this article, I use the depiction of literacy in the film as a lens through which I examine both the role of literacy in compounding the challenge for those already made vulnerable by their circumstances, as well as the creative, collaborative and resourceful ways in which individuals use literacy practices to navigate everyday lives. The release of I, Daniel Blake comes at a time when the threat to social justice posed by austerity politics is becoming an acute reality for many in Britain, and across the globe. I argue for the continued importance, therefore, of the critical examination of the relationship between literacy, inequalities and justice.